2020
DOI: 10.1371/journal.pone.0234055
|View full text |Cite|
|
Sign up to set email alerts
|

Defining the volume of consultations for musculoskeletal infection encountered by pediatric orthopaedic services in the United States

Abstract: Adequate resources are required to rapidly diagnose and treat pediatric musculoskeletal infection (MSKI). The workload MSKI consults contribute to pediatric orthopaedic services is unknown as prior epidemiologic studies are variable and negative work-ups are not included in national discharge databases. The hypothesis was tested that MSKI consults constitute a substantial volume of total consultations for pediatric orthopaedic services across the United States. Study design Eighteen institutions from the Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…22 Following implementation of this clinical pathway, our institution has the highest rate of pathogen identification for pediatric MSKIs described with 75% to 79% of acute MSKIs having a bacterial cause identified as compared with the national average of 37%. 23 However, this means 20% to 25% of our MSKI patients still remain culture negative despite our best efforts to uncover a bacterial culprit. 3,15,16,19 Identifying distinguishing characteristics of patients with culture negative MSKIs might help explain this apparent limit to our diagnostic yield.…”
mentioning
confidence: 99%
“…22 Following implementation of this clinical pathway, our institution has the highest rate of pathogen identification for pediatric MSKIs described with 75% to 79% of acute MSKIs having a bacterial cause identified as compared with the national average of 37%. 23 However, this means 20% to 25% of our MSKI patients still remain culture negative despite our best efforts to uncover a bacterial culprit. 3,15,16,19 Identifying distinguishing characteristics of patients with culture negative MSKIs might help explain this apparent limit to our diagnostic yield.…”
mentioning
confidence: 99%
“…While there was only 1 case of MRSA in our shoulder septic arthritis group, MRSA was the most commonly identified organism on their intraoperative tissue cultures. Reasons for this likely include the older average age of the children in their study and the higher prevalence of MRSA musculoskeletal infections in the geographic region in which their study was performed 15…”
Section: Discussionmentioning
confidence: 99%
“…After Institutional Review Board approval and the completion of data use transfer agreements from each institution, a multicenter retrospective review of medical records was performed at 18 participating institutions to create a database of patients aged ≤18 years with musculoskeletal infection 15. The group consists of pediatric orthopaedic surgeon principal investigators at university-affiliated and stand-alone children’s hospital systems across the United States.…”
Section: Methodsmentioning
confidence: 99%
“…A multi-center study recently reported that 10 percent of pediatric orthopaedic consultations were for musculoskeletal infection and that culture-positive confirmation of infection occurred in only 37% of cases. 15 Accurate diagnosis of children with signs and symptoms of musculoskeletal infection is challenging due to the tremendous overlap of symptoms, physical findings, and inflammatory markers between infectious and noninfectious conditions. Daniel Kahneman recently explored the extent to which judgment under uncertainty, particularly predictive judgment, is subject to noise, bias, and objective ignorance in modern healthcare.…”
Section: Discussionmentioning
confidence: 99%